Uso de práticas de inteligência competitiva no setor de móveis planejados - Minuzzi, Guilherme (Universidade do Vale do Rio dos Sinos, 2014)
A new economy based on information and knowledge, has been shaped. Competitive Intelligence is the central theme of this paper, which aims to analyze how customized furniture manufacturers apply Competitive Intelligence´s techniques and concepts on the practice of environmental monitoring and formulating business strategies. In addition to analyzing these practices, it is also an objective of this paper proposing a practical model technique to monitor the environment. To achieve the objectives proposed in this paper, qualitative research, presented through an exploratory study method, was used, where in-depth interviews were conducted with managers of furniture manufacturing companies and also with representatives of entities dedicated to this segment. The results show that the practices of Competitive Intelligence are still little used by furniture companies with regard to monitoring and making marketing decisions. Due to its industrial vocation, there is often greater attention to issues relating to product and production, which are the most developed areas of this sector. In general, strategies are made based on personal perceptions of managers, and market monitoring is not done by the management of these companies, but rather by the sales team, who can provide information on deviations of perception. The study concludes that there are few companies that practice environmental monitoring proactively and using the information collected in developing business strategies. There must be a better understanding by managers about the benefits of Competitive Intelligence to organizational performance, since nowadays is quite incoherent note that there are companies that make decisions based on personal feelings yet, rather than market information.
Keywords: Inteligência competitiva; Monitoramento ambiental; Estratégia; Competitive intelligence; Environmental monitoring; Strategy